The Integration of Character Education in Freedom Writers Movie into ELT Materials - Ganda Herdiansyah; Januarius Mujiyanto; Mursid Saleh (Universitas Negeri Semarang, 2022)
Education is necessary for students who are not only oriented to master subject matters but also to focus on character development. All students seemed to pursue value, rank, or medals, whereas the process of creating an actual character is more important than academic achievement. As a result, students grow up to be smart but characterless. The present study aims to explain the integration of character education in the Freedom Writers movie into ELT materials. These mixed methods study deeply investigated character education in the film which mean this research applying both quantitative data to calculate the frequency of the data and qualitative data to explain the results of the data. The data are dialogues and actions reflected on all the movie characters. The data were collected using theory of Bialik et al. (2015). The study shows that ethics is the most commonly found in the movie (81 items), followed by curiosity (80 items), mindfulness (59 findings), leadership (20 items), courage (19 results), and resilience (7 items). Moreover, the findings show the existing strengths in integrating character education into ELT materials for the students by adapting Model of Russell (2009). Hopefully, this research contributes as a reference to integrating character education into ELT materials.